On J-Cone Metric Spaces over a Banach Algebra and Some Fixed-Point Theorems - Jerolina Fernandez; Neeraj Malviya; Vahid Parvaneh; Hassen Aydi; Babak Mohammadi (Advances in Mathematical Physics)
In the present paper, we define J-cone metric spaces over a Banach algebra which is a generalization of Gpb-metric space (Gpb-MS) and cone metric space (CMS) over a Banach algebra. We give new fixed-point theorems assuring generalized contractive and expansive maps without continuity. Examples and an application are given at the end to support the usability of our results.